ANALYSIS OF CONTINUANCE USE INTENTION OF TIKTOK AS EDUCATIONAL INFORMATION WITH EXPECTATION CONFIRMATION MODEL (ECM) AND INFORMATION SYSTEM SUCCES MODEL (ISSM) - Nanda Nazira; Syaifullah, Syaifullah; Megawati, Megawati; Saputra, Eki; Marsal, Arif (Informatika, Universitas Jenderal Soedirman, 2024)
Social media is one of the main technologies currently used by billions of people around the world, especially TikTok. TikTok contains popular content such as comedy, dancing, and increasingly educational information. TikTok presents the #SerunyaBelajar program with 1.4 million posts. Despite the existence of interesting programs, problems were found such as inappropriate keywords about education, short video duration, inconsistent quality of information and distraction. So TikTok needs to focus on user satisfaction and retention by continuing to innovate. The purpose of this study is to measure satisfaction and intention to continue using TikTok as educational information. This study uses 2 models, namely the Expectation Confirmation Model with four variables (confirmation, perceived usefulness, satisfaction, and intention to continue) and the Information System Success Model with two variables (system quality and information quality). Respondents used totaled 96 TikTok users who accessed educational content and were processed using SEM-PLS. This study found that confirmation (T: 19.558) affects perceived usefulness. Thus, many users feel that TikTok provides useful features. In addition, satisfaction (T: 6.364) and continuance intention (T: 3.602) are influenced by perceived usefulness related to TikTok. And satisfaction (T: 3.809) influences TikTok users' continued intention to access educational content..